RICARDO’S MANIA LOVE IN MARIO VARGAS LLOSA’S THE BAD GIRL (LITERA KULTURA : Journal of Literary and Cultural Studies, 2014)
RICARDO’S MANIA LOVE IN MARIO VARGAS LLOSA’S THE BAD GIRL Deny Dwi Susanti English Literature, Faculty of Languages and Arts, Surabaya State University ddwisusanti@yahoo.com Drs. Much. Khoiri, M.Si English Department, Faculty of Languages and Arts, Surabaya State University much_choiri@yahoo.com Abstrak Penelitian ini difokuskan pada cinta mania Ricardo dalam novel The Bad Girl oleh Mario Vargas Llosa. Cinta mania ditandai dengan emosi pada diri sendiri, upaya putus asa untuk memaksa kasih sayang dari sang kekasih, dan ketidakmampuan untuk percaya atau mempercayai kasih sayang yang dicintai sebenarnya. Pecinta mania adalah seseorang yang memiliki hiper ekspektasi yang terobsesi terhadap seseorang tanpa persetujuan tertentu diantara keduanya. Tujuan dari penelitian ini adalah untuk menggambarkan bagaimana cinta mania Ricardo tercermin dalam novel The Bad Girl oleh Mario Vargas Llosa, untuk mengungkapkan faktor-faktor apa yang membuat Ricardo memiliki cinta mania, dan untuk mengungkapkan dampak cinta mania Ricardo dalam novel. Penelitian ini menggunakan teori John Alan Lee dan Sternberg untuk menganalisis novel tersebut. Akhirnya, analisis penelitian ini menghasilkan tiga temuan. Temuan pertama adalah bahwa cinta mania yang dialami oleh Ricardo ini sejalan dengan jenis cinta yang dinyatakan oleh Lee dan Sternberg. Temuan kedua menunjukkan bahwa ada tiga faktor yang memicu cinta mania Ricardo; yaitu merasa sedih, kepercayaan diri yang rendah, dan kehidupan sosial yang buruk. Untuk temuan terakhir, ada tiga hal yang mempengaruhi kehidupan Ricardo yaitu efek fisik, efek psikologis, dan efek sosial. Efek-efek tersebut yang mempengaruhi Ricardo sebagai pecinta mania selama terobsesi terhadap gadis nakal. Kata Kunci: cinta mania, cinta obsesif Abstract This study focuses on Ricardo’s Mania Love in Mario Vargas Llosa’s The Bad Girl. Mania love is characterized by self-defeating emotions, desperate attempts to force affection from the beloved, and the inability to believe in or trust any affection the loved one actually does display. The manic lover is someone who has a hyper expectation to obsess a person without a certain aggreement on both sides. The purposes of the study were to describe how Ricardo’s mania love is reflected in Mario Vargas Llosa’s The Bad Girl, to reveal what factors make Ricardo have his mania love, and to reveal the impacts of Ricardo’s mania love in the novel. The study used John Alan Lee and Sternberg theories to analyze the novel. Eventually, this analysis of this study resulted in three findings. The first finding was that mania love which was experienced by Ricardo was in line with the types of love stated by Lee and Sternberg. The second finding showed that there were three factors which trigger the Ricardo’s mania love; namely feeling down, low self confidence, and poor social life. For the last finding, there were three things which affect Ricardo’s life. They were physical effect, psychological effect, and social effect. Those effects affected Ricardo as the manic lover as long as he obssessed for the bad girl. Keywords: mania love, obsessive love INTRODUCTION Love has always been a favorite topic for poets, novelists, and songwriters. It has always relationship with literature. And it is difficult to imagine literature without love. Love becomes so universal theme because of the remarkable variety of its world. Nothings else human being so impatically declares at the same time the plurality of living (Bayley in Mardianto, 2008:1). It is an emotion that nearly everyone has experienced in their life. Because the main purpose of life is to be happy and there is only happiness in life, that is love and to be loved. Literary work is a reflection of the real world. By studying the human literature we can also learn the real life world. It means to study the character of the same in the literature by studying real human character. Literary work presents a wide range of people including the possible odd or taboo if discussed. To learn it let us see the work of a famous writer Mario Vargas Llosa. Mario Vargas Llosa’s recent novel The Bad Girl centers around of love. Of course, there are a lot of literary work which uses love as the main theme. But, in this novel the reader will be brought to Ricardo’s love. Sobur said that love is a common thing in human being. Because everyone has through the love experienced in their life. And according to Watson that basically, human has three basic emotions. They are fear which can develop into anxiety, rage which can develop into anger, and love which can develop into sympathy. (Meliana, 2008:2). Everyone has an emotion to be developed, such as in anxiety, anger, or love. It depends on the people in driving their emotion. The Bad Girl is the novel which is translated by Edith Grossman, the winner of the 2006 PEN/Ralph Manheim Medal for Translation, is the translator of many works by major Spanish-language authors, including Gabriel García Márquez, Mayra Montero, and Miguel de Cervantes, as well as Mario Vargas Llosa. She lives in New York City. Additional praise for The Bad Girl, Chicago Tribune Favorite Book of 2007 and San Francisco Chronicle Notable Book of 2007. "Splendid, suspenseful, and irresistible . . . A contemporary love story that explores the mores of the urban 1960s and 70s and 80s.” -The New York Times Book Review- “Perversely charming... Irresistibly entertaining.” -The Washington Post Book World- Llosa has many awards, one of his nobel prize such as The Bad Girl that published by Alfaguara, Spain as Travesuras de la Niña Mala in 2006 which has won nobel prize in 2010. So, there is no doubt to choose his work to be analyzed in this study. The Bad Girl is begun with Peruvian Ricardo Somocurcio from the summer of 1950 when, as a teenager, he meets ‘the bad girl’ for the first time and he fell in love with her. “I like everything about you,” it showed that Ricardo really loved her so much. He expressed his love in three times and he fell in three times, too. He continuosly made effort in order to make the girl together with him untill she disappeared without explanation. In accordance of background study above, it can be simplify to discuss among three problems that emerge as significant concern toward this novel. How is Ricardo’s mania love reflected in Mario Vargas Llosa’s The Bad Girl? What factors make Ricardo have his mania love in Mario Vargas Llosa’s The Bad Girl? What are the impacts of Ricardo’s mania love in Mario Vargas Llosa’s The Bad Girl? The problem can be analyzed using psychological approach as the base of the guide and theory. Those statements will use the concept of love, obsession, and obsessive love. RESEARCH METHOD Research methodolgy that used in this analysis here must be qualified as an applying in literary appreciation. The thesis is regarded as a descriptive-qualitative study and uses a library research. This study uses novel of Mario Vargas Llosa entitled The Bad Girl that published Picador, New York in 2007 as the data source of this study. The data are in the form of direct and indirect speech of the characters, dialogues, epilogues and quotations which indicates and represents aspect of representation of Ricardo’s mania love, the factors make Ricardo’s have his mania love, and the impacts of Ricardo’s mania love in the novel. This thesis is using the library method in collecting the data. It does not use the statistic method. That is why it is not served in numbering or tables. Library research used an approach in analyzing this study. The kind of library research which is used here is intensive or closely reading to search quotations or phrases. It also used to analyze the literary elements both intrinsic and extrinsic. The references are taken from library and contributing ideas about this study from internet that support the idea of analyzing. The analysis is done by the following steps: (1) Classification based on the statement of the problems. This classification is used to avoid the broad discussion. (2) Describing representation of Ricardo’s mania love which is stated from the quotations and statements by using concept of love. (3) Revealing the factors make Ricardo have his mania love. (4) Revealing the impacts of Ricardo’s mania love. The quotations that showed how Ricardo’s life is affected by mania love are taken as data. (5) Drawing the conclusion based on the analysis which is in line with the problems. ANALYSIS The first section is about the reflection of Ricardo’s mania, is the main character in this story. Love is the main point in this novel. The Bad Girl is a story which tell about Ricardo Somocurcio was in love with a bad girl called Lily as a coy teenager in Lima in 1950. She disappeared without explanation and he loved her still when she reappeared again. The feeling of Ricardo’s love is showed by words like a calf, hundred degrees, and fell three times that agree with Sternberg, the characteristic of love which manic lover are irrational by thoughts of their lovers, affection, and defensiveness. His statement is very nice to be declared toward the girl who he loved. “I fell in love with Lily like a calf, which is the romantic way to fall in love– it was also called heating up to hundred degrees– and during that unforgettable summer. I fell three times.” (Llosa, 2007:5) In the quotation above a calf can be defined as a young bovine animal, especially a domestic cow or bull in its first year. The character of Ricardo that was compared with a calf which is obedient, obey to the intructions of its boss, not comment in everything he wanted, and let the boss to do anything toward its self. That behaviour showed that what he did in his life have a quality of irrational. According to him that fall in love like a calf was the romantic way to fall in love. So, he compared himself with a calf when he felt it. Later heating up to hundred degrees. When someone fall in love in temperature a hundred degrees, it showed that he had a deep feeling to his lover. A hundred degrees was very high temperature normally. It had high heat like as boiling water. It proved that the feeling of love was very deep and true. That is called affection, the deep feeling of love. The next was fell three times. It had mean that Ricardo intends to defend or protect himself which he was refused by the bad girl. The purpose is to give information to Lily that he will never surrender to defend his love for her although she has refused him as many as three times. Whereas usually arround our life most of people when he or she is failed or refused by her or his lover, people would look for the other than they have to suffer from his or her feeling. But, here Ricardo defended his love still she reappeared again. The characteristics of mania love besides irrational and defensiveness, it also has obsession. It can be proven by a quotation below. Ricardo relizes that he very want to get the bad girl as his lover, although his feeling occured ten years ago. He always thinking about her every time. That can be seen from this quotation: “I grasped her hand and, interlacing my fingers with hers, asked if I realized I’d been in love with her for ten years.” (Llosa, 2007:23) Agree with the mania love which obsessive that is said by Lee, Ricardo made an effort to make sure the bad girl that he always love her as long as ten years. It happened after he met the bad girl as Comrade Arlette. Although ten years ago he fell in love with Lily, he never could forget Lily and kept her always in his mind. It could be an evidence that his love as obsession. If someone has an obsession toward something, he would not surrender before he could get what he wanted or before he succed. After Ricardo fell three times, he encouraged himself to declare his feeling again. He never get the answer certainly. Besides affection which declared in romantic way, he compared himself with a calf which would do anything or obey what employer /boss wanted. "We'll see." And she blew me a kiss and moved away. "Never lose hope, good boy." (Llosa, 2007:24) The bad girl never said yes or no toward Ricardo. She declared a challenge to him by saying “we’ll see” and “never lose hope, good boy.” It showed that she gave a hope to him and proved of playful love. She regarded Ricardo’s love was just a play. That agree with John Lee’s six styles of love said that mania love is a combination of eros and ludus love, which eros that has tremendous passion, physical longing, deep intensity and intimacy and ludus called playful love. So, these statements of the girl above showed that it proved Ricardo’s love full of playing. It is proven by an action of the woman (kissing the man) and her saying toward the man (challenge words). The manic lover is someone who has a hyper expectation to obsess a person without a certain aggreement on both side. He (she) lacks the self-confidence associated with eros and the emotional self-control associated with ludus. They also imagine future with beloved. He can be obsessive toward belove as long as he never get him/her yet. It could be seen from qoutation below as an evidence that manic lover always imagine future with beloved although they was not recognized. “The fact that they were poor and embarassed by everything they didn’t have filled me with compassion, increase my love for the Chilean girl, and inspired me with altruistic plans: “When Lily and I get merried, we’ll bring her whole family to live with us.” (Llosa, 2007:10) Lee said that the manic lover was desperated to fall in love and to be loved, begins immediately to imagine a future with the partner. For Ricardo, fell three times was not make him leave his feeling toward the bad girl when she was named Comrade Arlette as the Guerilla Fighter in that time. Exactly he had compassion on her. He wanted the bad girl to live with him in the future. So, the quotation above could be an evidence which indicate mania love. As liked was imagined by Ricardo to have a future with his beloved, it could be increased Ricardo’s love feeling toward his beloved. So, it made him wanted to have the woman more and more. Mania love also indicated by forcing of manic lover. He tried to force the partner to show love and commitment. He attemppted to persuade his partner to recognize his existence and showed her commitment to love him. Liked as this quotation below which Lee said before that manic lover dependent on his beloved. “You have to leave that gentleman right away and marry me,” I told the Chilean girl the next time we saw each other. “Do you want me to believe you’re in love with a Methuselah who not only looks like your grandfather but is very ugly too?” (Llosa, 2007:48) Ricardo desperate attempts to force affection from the beloved, moreover he knew that Madame Arnoux or the bad girl or his beloved’s marriage to diplomat was a mere formality to which she has resigned herself in order to leave Cuba and settle in Paris. Ricardo is seemed in a good condition, because he very believed that one could make any sacrifice for the sake of Paris. But, when they were alone, she should not play the faithful, loving wife, because they both knew very well it was a fairy tale. Even though she was legally married to a French citizen, she could not get French natioanlity for two years. Ricardo’s effort was just not once for asking the bad girl to make commitment with him, but it was in many times. He tried and tried continuing to make the bad girl showed her love to him. Mania love is obsessive, the manic lover has to possess the beloved completely. In return, the manic lover wishes to be possessed, to be loved intensely. They tend to feel that their poor self esteem with only improve with intense love. Their sense of self-worth comes from being loved, rather than from inner satisfaction. (retrieved on April 1, 2014 at 16.30, from http://valarie-king.hubpages.com/hub/Understanding-Different-Types-of-Lovers) The second section will show the factors make Ricardo have his mania love. Obsession define as thinking about something or someone too much or in a way that is not normal, having an obsession it mean showing or relating to an obsession. When obsessed, an individual continues the obsession in order to avoid the consequent anxiety. Then love which is influenced by obsession is called obsessive or mania love. Obsessive love is a form of love where one person is emotionally obsessed to another. There some factors that cause person madly in love with someone, then he or she is obsessed to the target. Ricardo’s mania love or obsessive love for the bad girl can be occured because he does not have enough of what he want. He always long for more love, more attention, more commitment, and more reassurance. And with the bad girl. Ricardo gets something that he can not be obtained from other woman. There are three factors of Ricardo’s mania love. The first is feeling down. A person that is feeling down is more susceptible to falling in love because they want someone to relieve them of their pain. If a person feels down enough, this love turns to obsessive love. Actually, when Ricardo begins to love the bad girl he is not in a feeling down situation. But when the bad girl leave him after they met, immediately Ricardo feels down of losing her. His inability to meet her makes him falls into a deep pain. Some women’s effort to make him happy is unsuccessful, because Lily, the bad girl is the only person who able to make him happy. Grief and sorrow that he faced during his days without the bad girl never make Ricardo stop loving her. The disappearance of the bad girl surer that his feeling for the bad girl can be said as love. there are no other women in the world who make him divert his attention from the bad girl because his obsession is only the bad girl. “The only one, Elena. The only woman I’ve loved, ever since she was a girl. I’ve done the impossible to forget her, but the truth is it’s useless. I’ll always love her. Life wouldn’t have meaning for me if she died.” (Llosa, 2007:172) Ricardo’s statement when he thought about the bad girl proved that he is very feeling down of losing her. His feeling toward the bad girl made him more obsessed for her. There is no other person who made him curable but the bad girl. He spent his times for only thought about her every moment. His obsessive love or mania love with the bad girl leads him into a deep sadness when he is unable to find her. The second is low self-confidence. A person with low self confidence will always need someone to care about them so that they feel worthy. We all want someone to care about us but people with obsessive love have an unhealthy amount of this want. Men usually have a high self-esteem. They always want to be a hero for women. When women need men’s help, they self confidence is getting higher. Ricardo as a man also has that mindset. He is happy and satisfied when a woman needs him. This obsession makes way is that there is a lack of self-confidence in the person which leads to insecurity, feelings of vulnerability, and a perceived failure in their relationships. That is why they resort to certain tactics of holding on to that person. Interestingly, the exact opposite can also stand true, where a person has an inflated sense of self, is egoistic and has feelings of being special and/or different, so when there is a failed relationship, the person becomes obsessed and wants to possess and control the other. Given to their lack of self-confidence, if there is any form of inequality with the partner, either in the social class or in the level of attractiveness, they might have the need to possess and gain control over the situation thus. “The twenty-year difference in our ages didn’t seem to trouble her. It did trouble me. I always told myself that our good relationship would diminish when I was in my sixties and she was still a young woman. Then she would fall in love with someone her own age. And leave. She was attractive in spite of how little time she spent on her appearence, and on the street men followed her with their eyes.” (Llosa, 2007:249) The perfection of Marcella makes Ricardo feels uncomfortable and lost his self confidence as a man. With Marcella he feels that he is useless. Marcella always be able to handle every problem by herself without Ricardo’s help. And he lives by her expense because he is not able to be a good translator again. He is bored of going the relationship on that way. Too many difference in their ages makes Ricardo seem to trouble her. Ricardo always told himself that their good relationship would diminish when he was in sixties and she was still young woman. Moreover she was attractive in spite of how little time she spent on her appearance, and on the street men followed her with their eyes. The third is poor social life. A person with a poor social life, and not many friends, can have a tendency to rely heavily on their partner to provide them with that missing social life. Again, this dependency can lead to obsessive love. After a long years he suffer of losing the bad girl, in the end he can not to be a good translation again. It makes him get bad payment. Unfortunately, that condition makes change in his life. He becomes alone and there is no friend to share with. Moreover after his friend, Paul left him alone. He feels sad and alone because he was the best friend he had during the uncertain times of his settling in Paris. “Fat Paul’s departure left me feeling empty because he was the best friend I had during those uncertain times of my settling in Paris.” (Llosa, 2007:37) His decision to stay in a hotel with a smaller room that his own before is a proof of his separation from social life. He looks better enjoy his day alone. Thinks about her, hunts about her, recalls his memories with the bad girl in past are the things which are considered by him as a therapy to relieve himself of losing the bad girl. Then, the last section will show the impacts of Ricardo’s mania love. there are three effects of Ricardo’s mania love. The first in physical effect. Obsessive love a part of love addiction, it can have physical consequences. Manic lover may engage in risky sexual behaviors in an attempt to maintain the interest of an avoidant partner. These risky behaviors increase the risk for hepatitis and other diseases. Love addicts may also experience bouts of physical pain, as the same areas of the brain are responsible for romantic love and pain perception. Failure is also makes Ricardo get an illness that make his body in imbalance. It begins after he get deep pain of losing the bad girl from his life. Depression affects his body in broken. He don’t care about his health. Until in that time he should experience a slight stroke. “The MRI established that I had suffered a slight stroke. That was the real reason for the neuralgia and dizziness.” (Llosa, 2007:254) Ricardo experiences for the neuralgia and dizziness, so it makes him has suffered from a slight stroke. Mania love or obsessive love brings many effect for Ricardo’s life. Start from physical effects, psycological effects, and social effects. Grief and sorrow take over Ricardo’s life until he never feels a happiness for his life. Then, In psychological aspect, the effects of love rejection is on the brain. This causes a manic lover to crave another person and quickly develop deep attachments to other people. These feelings may manifest themselves as physical pain or emotional pain. It can involves the same areas of the brain as other types of addiction. People struggling with manic lover may start drinking more than usual as a way to cope with their emotional pain. A love rejection of the bad girl makes Ricardo suffer from a deep pain and sorrow. Nothing that he can do except only thingking about the bad girl again and again. Until it makes Ricardo always has an illusion about the bad girl in everytime. “Because of her, the illusions that make existence something more than the sum of its routines had been extinguished for me. At times I felt like an old man.” (Llosa, 2007:152) Ricardo has illusion about the girl because of her helpless. According to Fromm, helplessness is a transitory condition, the ability to stand and walk on one's own feet is the permanent and common one Everything that Ricardo did was not give a pleasure anymore. It influented in his working as a translator. He felt that his life is useless. Mania love or obsessive love affects family relationships, friendships, and romantic relationships. When family members and friends point out addictive behavior, the manic lover may respond with aggression and hostility. The partners may verbally or physically abuse one another. When the relationship ends, the manic lover experiences reduced self-esteem and exhibits self-destructive behaviors. Ricardo as the manic lover avoid his family to know his true relationship with the bad girl. That his uncle know is he and his wife are fine. There is no trouble in his marriage. “I never told Uncle Ataulfo my marriage had failed, and so in his letters, until the end, he would send regards to “my niece,” and I, in mine, sent hers to him. I don’t know why I hid it from my uncle. Perhaps because I would have to explain what had happened, and any explanation would have seen absurd and incomprehensible to him, as it did to me.” (Llosa, 2007:251) Ricardo avoid to give knowing that his relationship has failed. He does not know how to explain what had happened to his uncle. One way that he take for his problem is he never told to uncle Ataulfo that his relationship has broken. His life will end unhappily and full of painful. Because in marriage, mania love can not hold out in a long time, but only in a short time they can enjoy their life in a joy. To cope with his broken relationship, the manic lover may avoid spending time with loved ones because he or she would rather spend time searching for a new romantic partner. Once a manic lover finds a romantic partner, the new relationship is characterized by a period of highs and lows. The new relationship starts with infatuation, which makes it difficult for the manic lover to see the romantic partner's flaws and shortcomings. Once this phase ends, the relationship is characterized by periods of melodrama and chaos. CONCLUSION The conclusion is divided into three in accordance to the statement of problems. From the analysis that has been done, it can be conclude in the first conclusion is the study reveals mania love or obsessive love which is employed by Ricardo as the main character of the novel toward the bad girl named Lily. Mania love or obsessive love has some characteristics or elements such as irrational, extremely jealous, obsessive, emotional, and often unhappy. By those elements it can be concluded that Ricardo’s love for the bad girl is mania love or obsessive love. It starts when Ricardo fall in love with the bad girl, Lily as a coy teenager in Lima in 1950. She disappeared without explanation and he loved her still when she reappeared again. From the analysis it can be concluded that there are two characteristics to be indicative of mania love or obsessive love. First, obsessive lovers believe that only the person they fixate on can make them feel happy and fulfilled. Second, person closed to the love obsessed can also be greatly affected. Witnessing a friend or family member suffer from the disorder can be distressing. The first characteristic is similar to Ricardo who has feeling of being comfortable and happy with the bad girl. Although there are some woman fill out his life with love it makes him is not as comfortable as when he together with the bad girl. For him the bad girl is the only woman he fixates on. The bad girl can make Ricardo happy and fulfilled. Because he begins in love with the bad girl, Ricardo is also affraid of losing her in his life. The second conclusion is that there are three factors of Ricardo’s mania love for the bad girl. The first is feeling down. Actually, when Ricardo begins to love the bad girl he is not in a feeling down situation. But when the bad girl leave him after they met, immediately Ricardo feels down of losing her. His inability to meet her makes him falls into a deep pain. Some women’s effort to make him happy is unsuccessful, because Lily, the bad girl is the only person who able to make him happy. Second is his low self confidence. The perfection of Marcella makes Ricardo feels uncomfortable and lost his self confidence as a man. With Marcella he feels that he is useless. Marcella always be able to handle every problem by herself without Ricardo’s help. And he lives by her expense because he is not able to be a good translator again. He is bored of going the relationship on that way. The last is Ricardo’s poor social life. After a long years he suffer of losing the bad girl, in the end he can not to be a good translation again. It makes him get bad payment. Unfortunately, that condition makes change in his life. His decision to stay in a hotel with a smaller room that his own before is a proof of his separation from social life. He looks better enjoy his day alone. Thinks about her, hunts about her, recalls his memories with the bad girl in past are the things which are considered by him as a therapy to relieve himself of losing the bad girl. The third conclusion is the impacts of Ricardo’s mania love for his life in the novel. In loving someone too much can give him or her some effects as if in his or her physical, psychological, and social life. First, in physical aspect Ricardo suffers from a slight stroke that caused by neuralgia and dizziness. Then, Ricardo get an illness of his mental health because of a deep pain and depression of losing the bad girl. The last is Ricardo mania love affects him in his social life. Ricardo avoid his family to know about his true relationship with the bad girl. He separated from social life with families, friends, and social life. From the explanation above it can be concluded that mania love or obsessive love is one types of love that dangerous. It can be seen from the reflection of Ricardo’s love for the bad girl by some characteristics of mania love. Many factors which cause Ricardo have his mania love and it brings many effects which affect Ricardo’s life such as in physical, psycological, and social effect. REFERENCES Ekawati, Sutri. 2008. Love, Sex, and Identity in Wei Hui’s Shanghai Baby. S1 Thesis, unpublished. Surabaya: State University of Surabaya. Fromm, Erich and Segal, Julia. 2009. Pengantar Umum Psikoanalisis Sigmund Freud. Yogyakarta: Pustaka Pelajar. Fromm, Erich. 1956. The Art Loving.pdf (retrieved on February 15, 2014 at 08.42) Gayatri, Nadia Nesha. 2012. Kemal’s Love in Orhan Pamuk’s The Museum of Innocence. S1 Thesis, unpublish. Surabaya: State University of Surabaya. Lee, John. 1973. John Lee’s Love Theory.pdf. (retrieved on November 4, 2013 at 20.53) Lewis, C.S. 1960. The Four Loves. Kansas: Public Library. Llosa, Mario Vargas. 2007. The Bad Girl. New York: Picador. Mardianto, Moh. Andik. 2008. The Study of love in George Eliot’s The Mill on The Floss. S1 Thesis, unpublished. Surabaya: State University of Surabaya. Meliana, Fahrinda. 2008. Kemal’s Oabsessive Love and Its Influence in His Sexual Motivation in Orhan Pamuk’s The Museum of Innocence. S1 Thesis, unpublished. Surabaya: State University of Surabaya. Minderop, Albertine Dr. 2011. Psikologi Sastra. Jakarta: Yayasan Pustaka Obor Indonesia. Regan. 2002. General Theory of Love. (retrieved on 14 March 2014 at 15.03) Sadrina, Farisah Nur. 2013. Philia Love in C.S. Lewis’ Narnia: The Lion, the Witch, and the Wardrobe. S1 Thesis, unpublished. Surabaya: State University of Surabaya. Internet Sources - http://nateperkins.com/kirbyguides/love.html (retrieved on 11 January 2014 at 10.25) - http://www.intrapsychictaxonomy.org/sternberg.htm (retrieved on 11 January 2014 at 10.26) - http://www.psikologizone.com/cinta-menurut-psikologi/065113807 (retrieved on 11 January 2014 at 10.29) - http://en.wikipedia.org/wiki/The_Four_Loves (retrieved on 11 January 2014 at 10.35) - http://www.buzzle.com/articles/obsessive-love-disorder.html retrieved on 11 March 2014 at 19.25